Student And Teacher Interaction Patterns In The Quran (Study of Surah Al-Baqarah Verses 30-31) - Achyar Zein; Syaukani Syaukani; Aan Afriansyah (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study aims to analyze the interpretation of the surah about the pattern of interaction between teachers and students in Q. S. Al-Baqarah verses 30-31. This study uses a qualitative method, using a library research approach. The primary data sources in this study were the Qur'an al-Karim and the books of interpretation, such as: Tafsir Al-Misbah, Tafsir Al-Wasith, Tafsir Jalalain, Tafsir Muyassar, Tafsir Ibn Kathir, Tafsir Al-Azhar, and Tafsir Al-Qur'an. The results show that the interpretation of Surah al-Baqarah verses 30-31 by mufassirin regarding teacher and student interactions can be described as follows: Interaction between teachers and students should be based on mutual understanding and must take place in an atmosphere of mutual respect. This attitude as shown by Allah swt as a teacher who makes a decision and angels as obedient and obedient students for what is the will of Allah is a reflection of a wise attitude in providing guidance or teaching to their students and students also have a sense of humility, obedience and obey the teacher. The pattern of interaction between teachers and students in Surah al-Baqarah verse 30 uses a two-way interaction pattern, namely reciprocal communication between teachers and students. Meanwhile, in Surah al-Baqarah verse 31, it uses a three-way interaction pattern (teacher-student-teacher-student pattern).